2019
DOI: 10.1186/s13046-018-0985-y
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum promotes chemoresistance to 5-fluorouracil by upregulation of BIRC3 expression in colorectal cancer

Abstract: BackgroundEmerging evidence suggests a potential relationship between gut microbiota and the host response to chemotherapeutic drugs including 5-fluorouracil (5-Fu). Fusobacterium nucleatum (Fn) has been linked to the initiation and progression of colorectal cancer (CRC). Unfortunately, little was known about the relationship between Fn infection and chemotherapeutic efficacy. Here, we investigate the potential relationship between Fn infection and chemotherapeutic efficacy of 5-Fu in CRC.MethodsDifferentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
182
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 54 publications
2
182
0
2
Order By: Relevance
“…Previous studies have reported that F. nucleatum contributes to the progression of colitis by damaging the integrity of colon epithelium and downregulating intercellular adhesion molecules, and that it also induces characteristic changes in macrophages in the colorectal tumor microenvironment [ 28 ]. Studies on the development and progression of CRC have shown that F. nucleatum promotes tumor formation as well as chemoresistance [ 29 ]. Although numerous works have reported the importance of F. nucleatum in the pathogenesis of UC and CRC, the role of F. nucleatum in the pathogenesis of CAC [ 30 ], which is the product of the close relationship between UC and CRC, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that F. nucleatum contributes to the progression of colitis by damaging the integrity of colon epithelium and downregulating intercellular adhesion molecules, and that it also induces characteristic changes in macrophages in the colorectal tumor microenvironment [ 28 ]. Studies on the development and progression of CRC have shown that F. nucleatum promotes tumor formation as well as chemoresistance [ 29 ]. Although numerous works have reported the importance of F. nucleatum in the pathogenesis of UC and CRC, the role of F. nucleatum in the pathogenesis of CAC [ 30 ], which is the product of the close relationship between UC and CRC, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum promotes colorectal cancer cell proliferation and tumorigenesis by activating Tolllike receptor 4(TLR4) signaling, which upregulates nuclear factor-κB, as indicated by increased MicroRNA-21 expression or the TLR4/p-PAK1/p-β-catenin S675-cascade signaling pathway (Yang et al, 2017;Wu et al, 2018). F. nucleatum promotes chemoresistance by upregulating BIRC3 expression and modulating autophagy in colorectal cancer (Yu et al, 2017;Zhang et al, 2019). In addition, in esophageal cancer tissue, F. nucleatum was associated with shorter times of survival for patients, which suggested the F. nucleatum has the potential to become as a prognostic biomarker (Yamamura et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have con rmed that alteration of intestinal ora can promote CRC development by inducing in ammation, immune suppression, and attacking the gut barrier system [19][20][21]. Moreover, intestinal ora has been proven to promote tumorigenesis and chemoresistance of CRC via regulating gene expression [22][23][24]. Therefore, the mechanism of intestinal ora contributing to the development of CRC is complex and multifaceted.…”
Section: Discussionmentioning
confidence: 99%